PENGARUH MORAL PAJAK, PENGETAHUAN PERPAJAKAN, DAN SOSIALISASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Yoni, Putu Risa Intan Purnama Padma; Widhiyani, Ni Luh Sari (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2025)
Taxes are the largest source of state revenue. Taxpayer compliance has a role in supporting state revenue. This research sought empirical substantiation concerning the influence of tax morale, knowledge, and socialization of individual taxpayer compliance at KPP Pratama East Denpasar and West Denpasar. The methodology employed for sample selection is classified as nonprobability sampling, specifically utilizing an incidental sample technique. The number for totaling individuals involved in the study was 100. Methods of data collection involved distributing questionnaires through a survey. This study employed Partial Least Squares-Structural Equation Modeling (PLS-SEM) for the analysis of data. Data underwent analytical procedures utilizing both SmartPLS 4 and SPSS. The output of this research shows that tax morale, knowledge, and socialization positively affect the compliance of individual taxpayers registered at KPP Pratama East Denpasar and West Denpasar. When morale is high, knowledge increases, and socialization becomes more intense, taxpayer compliance rises as well. This study supports attribution theory and compliance theory, showing that individual behavior has an impact on taxpayer compliance.